1998
DOI: 10.2337/diabetes.47.5.831
|View full text |Cite
|
Sign up to set email alerts
|

A functional analysis of the role of IGF2 in IDDM2-encoded susceptibility to type 1 diabetes.

Abstract: Genetic studies have identified a number of loci demonstrating linkage to type 1 diabetes. One of the largest single contributors to genetic susceptibility, after the major histocompatability complex, is the IDDM2 locus, which maps to a nontranscribed variable number of tandem repeats (VNTR) minisatellite upstream of the insulin (INS) and insulin-like growth factor 2 (IGF2) genes. In a progression from population to functional studies, recent reports have shown that VNTR susceptibility alleles (class I) have d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 29 publications
1
19
1
1
Order By: Relevance
“…Paquette et al [58] found an association between class I alleles of the INS promoter VNTR and increased expression of IGF2 in placenta, and it has been suggested that IGF2 expression may have some effect on intrauterine growth and birth size, both of which are known T1D risk factors [59]. However, this finding has not been confirmed in other studies [60,61].…”
Section: Igf2contrasting
confidence: 43%
“…Paquette et al [58] found an association between class I alleles of the INS promoter VNTR and increased expression of IGF2 in placenta, and it has been suggested that IGF2 expression may have some effect on intrauterine growth and birth size, both of which are known T1D risk factors [59]. However, this finding has not been confirmed in other studies [60,61].…”
Section: Igf2contrasting
confidence: 43%
“…However, Vafiadis et al 31 found the IGF2 ApaI G allele (associated with increased BMI in our studies) was associated with significantly higher IGF2 mRNA levels than the A allele, but unlike Paquette et al in placenta and liver cells, found no difference in expression of leukocyte IGF2 with respect to INS VNTR class I/III genotype, as they had previously established in thymus and pancreas. 32 Since our results show no association between INS VNTR I vs III classification and BMI, but substantial association with class I small subclass alleles (in coupling with IGF2 ApaI A alleles) versus large subclass alleles (in coupling with IGF2 ApaI G alleles), a precise aetiological chain between IGF2 and INS mRNA and hormone expression and protection from obesity (the IGF2 ApaI A/INS VNTR class I small subclass haplotype) cannot yet be inferred, although its genetic susceptibility is already measurable. The most plausible hypothesis may be that there is increased average transcription and IGF-II secretion from liver.…”
Section: Discussionmentioning
confidence: 99%
“…Because the accuracy of competitor concentration may not be absolute, the data are presented as transcriptto-housekeeping ratio. The linearity of the PCRs and the appropriate concentration of competitors to be used were determined as described by Vafiadis et al (23). Immunoblotting and immunoprecipitation.…”
Section: Methodsmentioning
confidence: 99%